Evolution and Trends in Biochar Research: A Bibliometric Analysis - Saucedo-Ibarra, Jahaziel; Sahagún-García, Alejandra; Cuevas-Reyes, Venancio; Ayala-Montejo, Diana; Baca-del Moral, Julio; Pérez-Nieto, Joel (REVISTA TERRA LATINOAMERICANA, 2025)
Sustainable technologies such as biochar are required to improve soil health, mitigate greenhouse gas emissions, increase soil organic carbon and productivity. Globally, there is abundant research on biochar, however it is scarce in Mexico, hence, it is necessary to identify international scientific trends for local application. The aim of our study was to analyze the temporal evolution and current trends in scientific research on biochar, especially its development, application and contributions to sustainability at a global level through a bibliometric approach from 2007 to 2022. A Scopus search was conducted on biochar development, application and sustainability, filtering by document type, subject area and stage of publication. A total of 1932 documents were analyzed using bibliometric indicators with bibliometrix and VOSviewer. An exponential increase in biochar research since 2007 was found. China and the United States stand out as the most productive countries. The journals with the highest number of articles were Agronomy and Biomass and Bioenergy. The af filiations with the most publications were Nanjing Agricultural University and Northwest A&F University in China. Recent research trends include topics such as carbon sequestration, methane, nitrous oxide and heavy metals. The keyword network analysis identified three thematic groups: characteristics and benefits of biochar in soil, sequestration of greenhouse gases and aspects of biochar production. Field research is needed to evaluate the positive and possible negative ef fects of biochar in order to determine its applicability in agriculture, taking into account economic, environmental and social aspects.